The Influence Of Personal Selling And Digital Marketing As Well As Buying Interest In Purchasing Decisions. Case Study Customer HousingGolden Waringin Karangploso Malang - Chasanah, Usfatul (Bulletin of Management and Business, 2024)
The purpose of this study was to determine the effect of personal selling, digital marketing, and buying interest on purchasing decisions in the Golden Waringin Karangploso property. The analysis used in this study is the Partial Least Square (PLS) analysis. Each of these hypotheses will be analyzed using smartPLS 3.2.9 software to test the relationship between variables. The methods and quantitative research instruments used are a questionnaire measured using a Likert scale. Respondents in this study were 40 respondents consisting of men and women with various age and occupation. The sampling technique used was purposive sampling. From the results of data analysis, the coefficient of determination (R Square) is 82,8%, so it means that personal selling, digital marketing and buying interest simultaneously have a significant effect. Partially Personal Selling has an insignificant effect but has a positive relationship direction. Digital Marketing variables have a significant effect and have a positive relationship direction. The Purchase Interest variable has a significant effect and has a positive relationship direction.